Molecular characterization and risk factors for carbapenem-resistant Gram-negative bacilli colonization in children: emergence of NDM-producing Acinetobacter baumannii in a newborn intensive care unit in Turkey - KEPENEKLİ KADAYİFCİ, EDA; ALTINKANAT GELMEZ, GÜLŞEN (W B SAUNDERS CO LTD, 2016)
Background: Multidrug-resistant Gram-negative bacilli are responsible for more than 50% of healthcare-associated infections. Colonization dynamics, characteristics, and risk factor data for CR-GNB are scarce in children. Aim: To examine the molecular characteristics of, and risk factors for nosocomial colonization with, carbapenem-resistant Gram-negative bacilli (CR-GNB) in hospitalized paediatric patients in a tertiary university hospital's paediatric units in Turkey. Methods: A prospective case-control study was performed at a university hospital in Istanbul, Turkey. Findings: A total of 1840 rectal swab specimens were collected from all 762 hospitalized children between March 2013 and October 2013. Among them, 176 (23%) patients were colonized with CR-GNB. Of these, 72 (9%) patients were colonized with carbapenem-resistant Enterobacteriaceae, 138 (18%) with CR-non-fermenter Gram-negative bacilli (CR-NF) and 34 (4%) with both. The median CR-GNB colonization time was 10 days (range: 1-116). The median duration of rectal colonization with CR-GNB was 8 days (range: 1-160). NDM (31%) was the second most frequent carbapenemase identified in Acinetobacter baumannii isolates, and has not previously been detected in Turkey. All of the 17 patients colonized with NDM-producing A. baumannii were newborns in the neonatal intensive care unit. Independent risk factors for CR-GNB colonization were: age <1 year, nasogastric tube placement, presence of underlying chronic diseases, ampicillin usage, surgical intervention, and carbapenem use.
Keywords: Acinetobacter baumannii; Carbapenem resistance; Children; Colonization; Gram-negative bacilli; NDM; METALLO-BETA-LACTAMASES; KLEBSIELLA-PNEUMONIAE; NOSOCOMIAL INFECTION; MULTIPLEX PCR; ACQUISITION; ENTEROBACTERIACEAE; GENES